Where we live matters: a comparison of chronic pain treatment between remote and non-remote regions of Quebec, Canada - Audet, Claudie; Zerriouh, Meriem; Nguena Nguefack, Hermine Lore; Julien, Nancy; Pagé, M. Gabrielle; Guénette, Line; Blais, Lucie; Lacasse, Anaïs (Frontiers in Pain Research, 2024)
Objective: Where a person lives is a recognized socioeconomic determinant of health and influences healthcare access. This study aimed to compare the pain treatment profile of persons with chronic pain (CP) living in remote regions to those living in non-remote regions (near or in major urban centers). Methods: A cross-sectional study was performed among persons living with CP across Quebec. In a web-based questionnaire, participants were asked to report in which of the 17 administrative regions they were living (six considered "remote"). Pain treatment profile was drawn up using seven variables: use of prescribed pain medications, over-the-counter pain medications, nonpharmacological pain treatments, multimodal approach, access to a trusted healthcare professional for pain management, excessive polypharmacy (≥10 medications), and use of cannabis for pain. Results: 1399 participants completed the questionnaire (women: 83.4%, mean age: 50 years, living in remote regions: 23.8%). As compared to persons living in remote regions, those living in non-remote regions were more likely to report using prescribed pain medications (83.8% vs 67.4%), a multimodal approach (81.5% vs 75.5%), experience excessive polypharmacy (28.1% vs 19.1%), and report using cannabis for pain (33.1% vs 20.7%) (bivariable p<0.05). Only the use of prescribed medications as well as cannabis remained significantly associated with the region of residence in the multivariable models. Discussion: There are differences in treatment profiles of persons with CP depending on the region they live. Our results highlight the importance of considering remoteness, and not only rurality, when it comes to better understanding the determinants of pain management.